Rehabilitation professionals' perspectives of factors influencing return to occupation for people with lower limb amputation in East, South, and Southeast Asian developing countries: A qualitative study - Sayeed, Md Shapin Ibne; Oakman, Jodi; Stuckey, Rwth (Frontiers in Public Health, 2023)
Objective To identify barriers and enablers for return to occupation (RTO) for people with lower limb amputation (LLA) in East, South, and Southeast Asian developing countries from the perspective of rehabilitation professionals. Methods A convenience sample of rehabilitation professionals working in Asian developing countries participated in online in-depth interviews between September 2021 and February 2022. Interview transcripts were analyzed and thematically coded to the modified Health Care Delivery System Approach (HCDSA) framework. COREQ guidelines were followed. Results Twenty-eight interviewees from 13 countries shared their experiences of factors related to RTO for people with LLA. Identified factors described barriers and facilitators for RTO at all four HCDSA framework levels. The “environmental” level had the most identified factors (n = 56) and the “care team” level the least (n = 31). Common environmental RTO challenges included cultural attitudes to women; lack of rural/remote services; inadequate numbers and regulation of rehabilitation professionals; inappropriate prosthesis; limited government support for rehabilitation, and reliance on charitable models. Conclusions Despite varied cultural, religious, and geographical characteristics, consistent factors impacting RTO were identified within these thirteen countries. Identified barriers to RTO underline the need for improvements throughout service systems from the acute-care focus on saving life without consideration of RTO, the rehabilitation focused primarily on mobility, to the lack of occupational rehabilitation services and supporting policy in these countries. These interlinked factors at different levels of healthcare service systems reinforce the importance of systems approaches to best utilize limited resources toward improving RTO in this region.